m6A epitranscriptomic modification in hepatocellular carcinoma: implications for the tumor microenvironment and immunotherapy - Liu, Fen; Liu, Qingbin; Li, Xianying; Wang, Yufei; Cao, Ruoyu; Zhang, Shiyu; Jiang, Shulong; Wu, Jianlin (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver malignancy and a leading cause of cancer-related deaths globally. The asymptomatic progression of early-stage HCC often results in diagnosis at advanced stages, significantly limiting therapeutic options and worsening prognosis. Immunotherapy, with immune checkpoint inhibitors (ICIs) at the forefront, has revolutionized HCC treatment. Nevertheless, tumor heterogeneity, immune evasion, and the presence of immunosuppressive components within the tumor immune microenvironment (TIME) continue to compromise its efficacy. Furthermore, resistance or non-responsiveness to ICIs in some patients underscores the urgent need to unravel the complexities of the TIME and to design innovative strategies that enhance immunotherapeutic outcomes. Emerging evidence has revealed the pivotal role of N6-methyladenosine (m6A), a prominent RNA methylation modification, in shaping the TIME in HCC. By regulating RNA stability and translation, m6A influences immune-related factors, including cytokines and immune checkpoint molecules. This modification governs PD-L1 expression, facilitating immune escape and contributing to resistance against ICIs. Advances in this field have also identified m6A-related regulators as promising biomarkers for predicting immunotherapy response and as potential therapeutic targets for optimizing treatment efficacy. This review examines the regulatory mechanisms of m6A modification within the TIME of HCC, with a focus on its impact on immune cells and cytokine dynamics. It also explores the therapeutic potential of targeting m6A pathways to improve immunotherapy efficacy and outlines emerging directions for future research. These insights aim to provide a foundation for developing novel strategies to overcome immune resistance and advance HCC treatment.